Analisis Kebijakan Pemerintahan Desa dalam Menangani Tindak Pidana Penyalahgunaan Narkotika di kalangan Remaja di Desa Sei Buluh Kecamatan Perbaungan Kabupaten Serdang Bedagai - Daulay, Raja Martua; Muhlizar, Muhlizar; Joharsyah, Joharsyah (Jurnal Ilmiah Penegakan Hukum, 2025)
This study examines village government policies in addressing drug abuse among adolescents. The study, conducted in Sei Buluh Village, Perbaungan District, Serdang Bedagai Regency, has seen a steady increase in the use of narcotics and illegal drugs (Narkoba) over the past five years. This study used a qualitative descriptive method. Research data were collected through a literature review that included reviewing and analyzing books, articles, texts, and relevant laws and regulations. Collect instruments such as interviews with relevant parties involved in the study. Then, the types and sources of data were categorized into two main types: primary data and supporting data. In order to process the research data, the researcher applied qualitative analysis techniques, namely data reduction, data presentation, and drawing and verifying conclusions. The results of the study indicate that the Sei Buluh Village government has taken concrete steps in developing local policies aimed at preventing drug abuse among adolescents. This demonstrates a serious effort in maintaining the security and welfare of village residents. In addition to prevention efforts, the village government must also maintain order by involving security forces and law enforcement in handling cases of drug abuse.